Ecological Literacy In The Era Of Digitalization - Lopulalan, Dortje L. Y.; Rolobessy, Mike J. (Teumulong: Journal of Community Service, 2024)
In the era of digitalization, the environment is one area of human life that is given little attention by most people. The aim of this activity is expected to be to create a society with a critical and creative mindset and outlook. The public can criticize information received from various social media and can be creative in implementing the information obtained. The method of implementing the activity is observation and joint discussion. The results obtained by ecological literacy as a form of measure of environmental awareness are something that must continue to be developed through various adaptations of available methods, conditions, instruments and facilities, either systematically through formal education or sporadically through various media. The process of transferring knowledge and information itself has now entered a new era called post-literacy. This era is driven by the development of digital technology which drastically changes the mode of interaction between humans and information